OPTIMALISASI HASIL TIGA VARIETAS SELADA (LACTUCA SATIVA L) DENGAN PEMBERIAN PUPUK ORGANIK CAIR DAN BAKTERI RHIZOSFER - Kadafi, Muamar; Karist Dwi Wibowo; Refki Sanjaya (Universitas Veteran Bangun Nusantara, 2024)
This study aims to determine the effect of dosing POC vegetable waste with rhizofite bacteria on three varieties of lettuce plants. This research was conducted in Mulyoagung Village, Dau District, Malang Regency. Altitude ± 600 m asl. The start of research will be carried out in May – July 2023. The design used is a factorial random group design (RAK) and is repeated three times. The first factor is the lettuce plant variety while the second factor is the dose of POC, (liquid organic fertilizer) in the first factor, lettuce varieties (F), consist of: F1 = butter lettuce, f2 = green curly lettuce, F3 = red curly lettuce. In the second factor, the dose of liquid fertilizer (K) consists of: K1 = 50 ml, K2 = 100 ml, K3 = 150 ml. The conclusion of this study was that at the age of 14, 21, and 28 days after planting (HST), there was a significant interaction in the number of leaves with the best combination obtained in lettuce butter varieties using 50 ml of liquid organic fertilizer (POC). This variety shows superior performance in growth compared to green curly lettuce and red lettuce varieties. Applying POC as much as 50 ml significantly affects the number of leaves at the age of 14, 21, and 28 HST, leaf area at 21 HST, and the wet and dry weight of the upper part of the plant. However, this feeding did not show a significant effect on the wet and dry weight of the roots.